Pemberdayaan Ekonomi Kreatif Berbasis Potensi Lokal Menuju Desa Mandiri - Daonil; Risyadi, Gilang; P, Achmad Mahardika Dwi A. P.; Sumantry, Daffa Habibie; Sugiartono, Abi Maulana; Azzahra, Nasywa Shafa; Siswoko, Aldy Putra Puji; Rabbani, Raihan Gading; Heriyanto, Arif Bentar Suganda; Tambunan, Aron Micael; Fauzan, Rahmat; Azahra (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
The Community Service Program (CSP) is a form of community service aimed at empowering local potential in a sustainable manner. The CSP activities conducted by Group 15 of the Bhayangkara University of Greater Jakarta in Margahayu Village, RW 012,RT 03, East Bekasi, focused on enhancing the capacity of micro, small, and medium enterprises (MSMEs) through business digitalization support. The main challenges faced by the community partners include low utilization of digital technology in business promotion and record-keeping, as well as limited educational and expressive spaces for children. The approach used includessocialization and direct mentoring, such as creating Google Maps accounts and online stores (e-commerce). Beyond the main program, the CSP team also supported religious activities for children organized by local institutions as a form of social participation and character development. The results of the activities show that MSME players are beginning to understand the importance of digital existence and are showing interest in continuing to develop their businesses online. Meanwhile, student involvement in children's social activities has had a positive impact on social cohesion and the strengthening of religious values in the surrounding environment. This program has made a real contribution to building a community that is economically independent and socially and spiritually strong. Therefore, it can be concluded that this KKN program has successfully increased the community's economic independence and strengthened social cohesion in RW 012 RT 03.